(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is about the theory previously studied in the course called Linguistics. In a way ties will be established between general principles of linguistics and concrete linguistic facts, in other words, theoretical knowledge will find its application in practice. The field of linguistics may be divided in terms of three dichotomies: synchronic versus diachronic, theoretical versus applied and micro linguistics. According to the micro linguistics view, languages should be analyzed for their own sake and without reference to their social function, to the manner in which they are acquired by children, to the psychological mechanism that underlie the production and reception of speech, to the literary and the aesthetic or communicative function of language.